Interpersonal sensitivity on college freshmen’s depression: A moderated moderation model of psychological capital and family support - Xu, Haibo; Peng, Lixin; Wang, Zhen; Zeng, Ping; Liu, Xin (Frontiers in Psychiatry, 2022)
Background The prevalence of depressive symptoms has become very high among college freshmen, with interpersonal sensitivity serving as an important predictor of depression. Combining internal and external positive resources can effectively prevent and alleviate depression. This study explores the moderating role of psychological capital (PsyCap) in the relationship between interpersonal sensitivity and depression, as well as the moderating effect of familial support on the conditional influence of PsyCap among Chinese college freshmen. Methods A cross-sectional mental health survey was performed and the anonymous self-reported questionnaires, including the Patient Health Questionnaire, interpersonal sensitivity subscale of Symptom Checklist-90, Psychological Capital Questionnaire 24, and Perceived Social Support from Family, were distributed to the freshmen. Pearson’s coefficient was employed to describe correlations between variables. The PROCESS macro and slope difference tests were used to explore the moderating role of PsyCap and family support in the relationship between interpersonal sensitivity and depression. Results The prevalence of depression among freshmen was 30.89% (694/2,247). The correlation analysis revealed that depression negatively related to PsyCap (r = −0.187, p < 0.001) and family support (r = −0.193, p < 0.001) and positively related to interpersonal sensitivity (r = 0.399, p < 0.001). The moderation analysis showed that PsyCap negatively moderated the positive relationship between interpersonal sensitivity and depression (β = −0.159, p < 0.001). We also found that family support played a moderating role in the conditional influence of PsyCap (β = 0.076, p < 0.01). The slope difference test further showed that family support weakened the effect of interpersonal sensitivity on depression in freshmen when they had low PsyCap. Conclusion More attention should be paid to freshmen’s mental health and interpersonal interaction problems. For freshmen with interpersonal sensitivity and depression, mental health departments can conduct PsyCap development interventions to alleviate psychological symptoms. Freshmen themselves should also seek family support in time, but those individuals with high PsyCap should seek an appropriate level of family support to maintain their autonomy.